2014
DOI: 10.17576/gema-2014-1401-08
|View full text |Cite
|
Sign up to set email alerts
|

Permasalahan Pertuturan Dalam Bahasa Arab Sebagai Bahasa Kedua

Abstract: ABSTRAKKajian ini dijalankan ke atas sekelompok pelajar yang mengikuti kursus kemahiran bertutur bahasa Arab, iaitu BA (LQS 0415) yang ditawarkan oleh CELPAD (Centre for Languages & Pre-University Academic Development), International Islamic University Malaysia (IIUM), Gombak, kepada pelajar yang membuat pengkhususan dalam Pengajian Islam dan Bahasa Arab (IRKHS). Kursus tersebut dilaksanakan bagi membantu meningkatkan prestasi akademik golongan pelajar melalui penguasaan kemahiran untuk bertutur bahasa Arab. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
2
12
0
2
Order By: Relevance
“…However, when they are given a higher level of difficult topics such as Arab countries' global issues, their speaking proficiency becomes diminished due to the lack of information and the related words. This situation coincides with previous studies which found that among the factors the students were unable to speak well was due to lack of vocabulary related to a particular topic [14]…”
Section: Spontaneous Speechsupporting
confidence: 92%
See 1 more Smart Citation
“…However, when they are given a higher level of difficult topics such as Arab countries' global issues, their speaking proficiency becomes diminished due to the lack of information and the related words. This situation coincides with previous studies which found that among the factors the students were unable to speak well was due to lack of vocabulary related to a particular topic [14]…”
Section: Spontaneous Speechsupporting
confidence: 92%
“…This disadvantage may be due to a weak level of Arabic language use. This is supported by the study by [14] indicating that 70% of students still cannot master Arabic speaking skills well even though they will become Arabic teachers after graduation. Students' weakness in speaking skills due to lack of vocabulary related topics and fear of Arabic grammar errors when speaking [15].…”
Section: Problem Statementmentioning
confidence: 66%
“…To face this global pandemic situation of COVID-19, with the birth of physical and social distancing policies and rules, language learning can be formulated by shifting to patterns of active collaborative interaction in online network systems. This pattern emphasizes the practice and learning activities on an ongoing basis that will produce language production and repetition of words in-depth because understanding and learning vocabulary in foreign language learning becomes an important part (Alqahtani, 2015;Daud & Pisal, 2014;Moghadam, Zainal, & Ghaderpour, 2012), besides also being the most critical element in improving language skills. In line with the practice and learning process, the process of collaborative active learning interactions becomes more directed, and the creation of a speaking environment can be realized even within the scope of online networks.…”
Section: Introductionmentioning
confidence: 99%
“…Arshad and Abu Bakar (2012) showed that a majority of students in the Islamic education field have not mastered speaking skill despite being exposed widely to the Arabic language since secondary school. Daud and Abdul Pisal (2014) showed that difficulty in the Arabic language had hindered student capabilities in activities requiring speaking skills. Students faced more problems completing individual assignments because they have to do them alone, shyness, lack of confidence and lack of interest.…”
Section: Literatur Reviewmentioning
confidence: 99%